Friendly settlements before the European Court of Human Rights theory and practice - Keller, Helen, 1964-; Forowicz, Magdalena; Engi, Lorenz (Oxford : Oxford University Press, 2010)
The European Convention on Human Rights has become bogged down by an enormous workload, and settling a case has become an attractive alternative to ordinary proceedings. This book provides a full overview of the Court's friendly settlements and suggest ways they could be improved.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Compromise (Law); European Court of Human Rights